Spatiotemporal patterns of fault slip rates across the Central Sierra Nevada frontal fault zone - Rood,DH; Burbank,DW; Finkel,RC (Earth and Planetary Science Letters, 2011)
Patterns in fault slip rates through time and space are examined across the transition from the Sierra Nevada to the Eastern California Shear Zone-Walker Lane belt. At each of four sites along the eastern Sierra Nevada frontal fault zone between 38 and 39° N latitude, geomorphic markers, such as glacial moraines and outwash terraces, are displaced by a suite of range-front normal faults. Using geomorphic mapping, surveying, and 10Be surface exposure dating, mean fault slip rates are defined, and by utilizing markers of different ages (generally, ~20ka and ~150ka), rates through time and interactions among multiple faults are examined over 104-105year timescales. At each site for which data are available for the last ~150ky, mean slip rates across the Sierra Nevada frontal fault zone have probably not varied by more than a factor of two over time spans equal to half of the total time interval (~20ky and ~150ky timescales): 0.3±0.1mm year-1 (mode and 95% CI) at both Buckeye Creek in the Bridgeport basin and Sonora Junction; and 0.4 +0.3/-0.1mm year-1 along the West Fork of the Carson River at Woodfords. Data permit rates that are relatively constant over the time scales examined. In contrast, slip rates are highly variable in space over the last ~20ky. Slip rates decrease by a factor of 3-5 northward over a distance of ~20km between the northern Mono Basin (1.3 +0.6/-0.3mm year-1 at Lundy Canyon site) to the Bridgeport Basin (0.3±0.1mm year-1). The 3-fold decrease in the slip rate on the Sierra Nevada frontal fault zone northward from Mono Basin is indicative of a change in the character of faulting north of the Mina Deflection as extension is transferred eastward onto normal faults between the Sierra Nevada and Walker Lane belt. A compilation of regional deformation rates reveals that the sp